Martian Atmospheric Thermal Structure and Dust Distribution During the MY 34 Global Dust Storm From ACS TIRVIM Nadir Observations. Issue 9 (25th September 2022) - Vlasov, P.; Ignatiev, N.; Guerlet, S.; Grassi, D.; Korablev, O.; Grigoriev, А.; Shakun, A.; Patsaev, D.; Maslov, I.; Zasova, L.; Luginin, M.; Trokhimovskiy, A.; et al.
Abstract: The Thermal InfraRed channel in honor of professor Vassili Ivanovich Moroz (TIRVIM) of the Atmospheric Chemistry Suite onboard ExoMars Trace Gas Orbiter has continuously monitored the Martian atmosphere from 13 March 2018 until 2 December 2019, covering almost a complete Martian Year (MY). In the nadir mode of observations, infrared spectra obtained by TIRVIM in the spectral range 600–1, 300 cm −1 permit retrievals of vertical temperature profiles from the surface up to 60 km of altitude, surface temperatures and column aerosol optical depths. Here we report the retrieved atmospheric thermal structure and the column dust content during the global dust storm (GDS) of MY 34 monitored from L s = 182.2° to L s = 211.8° (Solar Longitude), capturing the evolution of the GDS and the response of the atmospheric thermal structure to the changing dust loading. The global storm caused asymmetric atmosphere heating, predominantly in the southern hemisphere, and changed diurnal contrast of atmospheric thermal structure. We also observe a reduced diurnal contrast of surface temperatures at the peak of the GDS. Plain Language Summary: The thermal radiation emitted by Mars in the spectral range 7.7–16.7 μm was measured by the Atmospheric Chemistry Suite Thermal InfraRed channel in honor of professor Vassili Ivanovich Moroz (ACS TIRVIM) onboard ExoMars Trace Gas Orbiter. The nadir spectra carry information about the temperature of the atmosphere at different altitudes thanks to a deep CO2 absorption present around 15 μm. Also, the dust loading can be found from the 9‐μm silicate absorption, and the surface temperature can be estimated at 7 μm where the atmosphere is mostly transparent. We follow the evolution of these parameters during the strong global dust storm of Martian Year (MY) 34 (2018). The peculiarity of the ACS TIRVIM data set is the exceptionally dense coverage providing a new look at this otherwise well‐studied dust event. Key Points: Atmospheric thermal structure and dust content on Mars are retrieved from Atmospheric Chemistry Suite Thermal InfraRed channel nadir measurements in the spectral range 7.7–16.7 μm The 2018 global dust storm covered the entire planet and caused an asymmetric heating of the atmosphere with a hotter southern hemisphere We observe a reduced diurnal contrast of surface temperatures and a changed contrast of atmospheric thermal structure during the storm